The influence of communication climate, organizational identification, and burnout on real estate agents’ turnover intention - Chun-Chang Lee; Yu-Ru Zheng; Wen-Chih Yeh; Zheng Yu (Humanities & Social Sciences Communications, 2023)
Abstract This study investigated the factors that affect the turnover intention of real estate agents by considering the impact of individual-level factors such as job stress, burnout, and salary level and team-level factors such as communication climate and organizational recognition. The parameters were evaluated using a hierarchical linear moderated mediation model. The survey subjects were real estate agents in Tainan City. A total of 870 questionnaires were distributed to 87 real estate agencies, and 615 questionnaires from 77 branches were collected. The questionnaires from four branches were excluded, as fewer than two questionnaires were collected, and an additional 57 questionnaires with missing responses were also excluded. A total of 558 questionnaires from 73 branches were included in the study. The overall response rate of questionnaires was 64.1%. The results indicated that the greater a real estate agent’s awareness of the communication climate, the higher the likelihood of the real estate agent receiving recognition from their organization, while a higher salary level indicated a lower level of turnover intention. A greater understanding of job stress indicated a higher risk of burnout. The communication climate had an impact on burnout and turnover intention, while organizational recognition mediated the impact of communication climate as it pertained to turnover intention. The results showed that the level of burnout mediated the impact of job stress and turnover intention.